1979
DOI: 10.3758/bf03208304
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception and the production of adaptation and intermanual transfer to prismatic displacement

Abstract: Proprioceptive adaptation to prismatic displacement and resultant intermanual transfer were investigated in two experiments. In Experiment 1, magnitude of adaptation and transfer were assessed as a result of the reduction of felt sensation via hypnotic anesthesia in an adapting limb. Such anesthesia reduced the magnitude of adaptation in that limb and resultant transfer in the nonadapting limb to a nonsignificant level. Such was not the case when the adapting limb was nonanesthetic. In Experiment 2, adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
3

Year Published

1984
1984
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
13
3
Order By: Relevance
“…In fact, goggle removal from the right side of the subject resulted in the production of "adaptation" at a level that significantly exceeded what would be produced by leaving the prisms over the subject's eyes for postexposure assessments (which is possible only with Risley prisms). Spanos et al (1983, p. 218) Wallace & Fisher, 1979;Wallace & Garrett, 1973, 1975 reporting nonsignificant results but in the direction we report here, it would appear inaccurate for them to claim that this constitutes a failure to replicate our earlier studies. With the large difference between our respective adaptation variances, it would seem prudent to determine why this occurred.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In fact, goggle removal from the right side of the subject resulted in the production of "adaptation" at a level that significantly exceeded what would be produced by leaving the prisms over the subject's eyes for postexposure assessments (which is possible only with Risley prisms). Spanos et al (1983, p. 218) Wallace & Fisher, 1979;Wallace & Garrett, 1973, 1975 reporting nonsignificant results but in the direction we report here, it would appear inaccurate for them to claim that this constitutes a failure to replicate our earlier studies. With the large difference between our respective adaptation variances, it would seem prudent to determine why this occurred.…”
Section: Discussioncontrasting
confidence: 56%
“…However, if proprioceptive feedback and felt arm sensations are disrupted as a result of inducing hypnotic anesthesia in the adapting limb, subjects fail to adapt to the prism displacement. We have argued that such anesthesia disrupts proprioceptive feedback from the arm and, as a result, adaptation does not occur (e.g., Wallace & Fisher, 1979). Spanos et al (1981) failed to replicate our effect; that is, they reported that adaptation to prism displacement occurs regardless of whether subjects are asked to perform a task with hypnotic anesthesia in the adapting limb or without it.…”
contrasting
confidence: 39%
See 3 more Smart Citations